Demystifying the compaction effects of TFC polyamide membranes in the desalination of hypersaline brine via high-pressure RO - Lim, Yu Jie (2024)
High-pressure reverse osmosis (HPRO) holds promise as a technology for the energy-efficient desalination of hypersaline brine (≥70 g/L total dissolved solids). In this work, we examined the effects of membrane compaction for four types of thin-film composite (TFC) RO membranes from DuPont Water Solutions (XLE, BW30, SW30HR, and XUS180808) using a crossflow filtration setup. The membranes were tested at a maximum applied pressure (ΔP) of 200 bar using a seawater desalination brine feed solution (70 g/L NaCl) to simulate conditions encountered in HPRO processes. Post-compaction membrane characterization revealed the densification of the support and selective layers of the TFC membranes (42–61% decrease in thicknesses and 15–22% reduction in polyamide heights, respectively) with respect to their pristine analogues. We also performed a mechanical strength analysis of the support layers that revealed the inverse relationship between the Young's modulus and magnitude of support layer compression. Our results suggest that support layers with a tensile strength ≥7 MPa and a Young's modulus ≥130 MPa are necessary to fabricate mechanically robust TFC membranes for HPRO application. In terms of desalination performance, the least compact-resistant membrane, XLE, displayed a drastic drop in water permeability and salt rejection from 1.63 L m−2 h−1 bar−1 and 97.5% in seawater RO test (ΔP: 55 bar, 35 g/L NaCl feed solution) to 0.39 L m−2 h−1 bar−1 and 95.0% in HPRO test (ΔP: 200 bar, 70 g/L NaCl feed solution). On the other hand, the most compact-resistant membrane, XUS180808, showed the least decline from 0.60 L m−2 h−1 bar−1 and 99.4% in seawater RO test to 0.35 L m−2 h−1 bar−1 and 99.2% in HPRO test. Overall, all four membranes showed irreversible decline in performance after HPRO tests whereby they could not regain their original permeability values at lower pressures (<200 bar).